Chandlerism in Post-War Europe: Strategic and Structural Change in France, Germany and the United Kingdom, 1950-1993 - Whittington, R; Mayer, M; Curto, F (1999)
This paper examines the Chandlerian model of corporate development in the light of new data on the strategies and structures of large European firms in the post-war period. Conglomerate strategies continue to spread, but these are typically less stable than strategies of diversification. The divisional structure now predominates in Europe, suppressing more indigenous forms. The paper discusses implications both for economic arguments around the resource-based view of the firm and for institutionalist arguments around the spread of American management ideas. The paper concludes that Chandler's original model is remarkably robust to both change over time and differences across countries.